EMOTIONAL FUNCTIONING OF CHILDREN AND ADOLESCENTS WITH CELLIAC DISEASE - stojanovićJovanović, biljana n; Jovanović , Stevan; Vuletić , Biljana (PONS - medicinski časopis, 2021)
The aim of the study: To investigate the difference between the subjective experience of signs of depression of children with celiac and their healthy peers and to obtain a comprehensive picture of the impairment of the emotional and social functioning of children with celiac disease in relation to healthy peers.Method of research: The research was conducted as  prospectively, observational study. The study included 116 participants aged 5-18 years with a diagnosis of celiac disease and 116 healthy children who met the basic criteria for "matching" with the examined group according to age and gender. Mood and Feelings Questionnaire Short - MFQ was used to assess the mood and discovery of depressive symptoms in children and adolescents.Results: In the gruoup of children with celiac disease there is a statistically significant greater preference for depression(p
Keywords: Celiac disease, children, gluten, nutrition, depression.